Awareness of Stroke Warning Signs Management Among Patients with High-Risk Hypertension - ตานันต์, รักนิรันดร์; คมพยัคฆ์, จริยาวัตร; สีขาว, อรพินท์ (Journal of Health Sciences and Wellness, 2018)
The purpose of this research was to study factors that affected the awareness of stroke warning signs and management of stroke warning signs in patients with high-risk hypertension. The sample was 285 patients who were diagnosed with high-risk hypertension at Outpatient Department of HuaChiew hospital. The research instrument was the questionnaire constructed by the researcher. The content validity was examined by three experts. The reliability was tested by Cronbach’s alpha coefficient which for awareness of stroke warning signs was at 0.775 , and for awareness of stroke warning signs management was at 0.810. The data collection was done approval of the after the Research Ethics Committee of Huachiew Chalermprakiet University. The data were analyzed by descriptive statistics and inferential statistics which included percentage, mean, standard deviation, and Pearson correlation coefficient at the significance level of 0.05. The results of the research related that the level of awareness of stroke warning signs management was high ( = 2.36, SD = 0.21), the awareness of level stroke warning signs was medium ( = 2.12, SD = 0.70) and the awareness of stroke warning signs was related to the awareness of stroke warning signs management with a statistical significant of p < 0.001